The Politics and Civics of National Service : Lessons from the Civilian Conservation Corps, VISTA, and AmeriCorps - Bass, Melissa (Book collections on Project MUSE., 2013)
In 1933 President Franklin D. Roosevelt created America's first domestic national service program: the Civilian Conservation Corps (CCC). As part of this program-the largest and most highly esteemed of its kind-nearly three million unemployed men worked to rehabilitate, protect, and build the nation's natural resources. It demonstrated what citizens and government could accomplish together. Yet despite its success, the CCC was short lived.